Reflections of Formal Education in Informal Classroom Culture: The Case of Latvia (1964–2004) - Valeina, Kitija (Acta Paedagogica Vilnensia, 2017)
The article describes the reflections of formal education in informal classroom culture in Latvia in the period from 1964 to 2004. The reflections of formal education are considered within different political regimes using two stages of the political system development in the history of Latvia, i.e., starting with the authoritarian regime of the Brezhnevian Stagnation Period to the collapse of the Soviet Union and the democratic period from the restoration of independence of the Republic of Latvia up to the accession of Latvia to the European Union. This article introduces the theoretical interpretation of the concept of informal classroom culture, which provides informatikon on the school of the past, school subjects, the class, classmates etc. up to modern times. Memory albums made by students and photographs were used as written and visual sources for the analysis performed within the research framework by aiming to answer the question of how the components of the education system (e.g., a student, a teacher, study materials and school subjects) are portrayed in the informal classroom culture sources. The research results reveal that the selected elements of formal education are directly or indirectly portrayed in informal classroom culture. Their use and presence are frequent, which substantiates the fact that formal education is a significant component of informal classroom culture.
Keywords: informal classroom culture; authoritarianism; democracy; memory albums; photographs